2017
DOI: 10.1080/09273948.2017.1299869
|View full text |Cite
|
Sign up to set email alerts
|

Anakinra in the Treatment of Patients with Refractory Scleritis: A Pilot Study

Abstract: This pilot study suggests the efficacy of anakinra in patients with refractory scleritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…The advent of biologic therapy has revolutionized the management of noninfectious intraocular inflammation. However, most of the reported literature is primarily focused in the treatment of uveitis [14], whereas the efficacy and safety of biologics in scleritis have mainly been addressed by single case reports and small case series [6][7][8][9][10][11]15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advent of biologic therapy has revolutionized the management of noninfectious intraocular inflammation. However, most of the reported literature is primarily focused in the treatment of uveitis [14], whereas the efficacy and safety of biologics in scleritis have mainly been addressed by single case reports and small case series [6][7][8][9][10][11]15].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported in other studies as well. Treatment with the interleukin-(IL-) 1 receptor antagonist anakinra resulted in a rapid improvement within 1 month in a case series of 10 consecutive patients affected by severe and refractory nonnecrotizing scleritis [7]. Silpa-Archa et al reported the achievement of inflammation control with steroid-sparing effect in 50% of their scleritis patients under the IL-6 inhibitor tocilizumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bottin et al 43 describen 10 pacientes con escleritis resistente a tratamiento inmunosupresor (tratamiento medio previo de 13 meses) a los que se trató con anakinra, antagonista de la interleucina 1. La tasa de respuesta completa fue del 90% a los dos meses de tratamiento.…”
Section: Tratamientounclassified
“…NLRP3 may be involved in lung fibrosis, and increased circulating levels of IL‐18 have been identified as a potential biomarker for interstitial lung disease in RA patients . Increased circulating levels of IL‐1β have been documented in patients with severe scleritis , and importantly, a recent small pilot trial has shown efficacy for anakinra in the treatment of refractory scleritis associated with systemic inflammatory disorders . Many autoimmune diseases also lead to an increased risk of cardiovascular disease, and the inflammasome contributes to this risk through its known effects on plaque progression, destabilization of plaque (for review, see ref.…”
Section: Introductionmentioning
confidence: 99%